Seed transmission of Xanthomonas campestris pv. translucens, the inducer of bacterial stripe and black chaff in barley - R.P. MAHARSHI*, HEMANT SHARMA and (Indian Phytopathology, 2006)
The role of infected barley seed in the transmission of X. campestris pv. translucens from season to season under Rajasthan conditions was established. The rate of transmission was found to be directly proportionate with rate of seed infection. Seed lot with even one percent infection was sufficient to lead to bacterial transmission between successive crops of susceptible cultivars of barley (viz. RD-2052 and RD2035). Infected seeds showed brown stripe discoloration with bacterial ooze. Sprinkler irrigation favoured the secondary transmission of the disease compared to conventional basin irrigation system.